The Isolation and Identification of Dengen Leaf Flavonoid Compounds (Dillenia serrata Thunb.) - Nurul Aulia Kaffi (Makassar Natural Product Journal (MNPJ), 2023)
The isolation and identification of flavonoid compounds of dengen leaves (Dillenia serrata Thunb.) has been carried out. The aim of this research was to determine the group of flavonoid compounds from the Dengen Leaves extract (Dillenia serrata Thunb.). A sample of 500 grams was macerated with ethanol solvent to produce 53.369 grams of dry extract with a yield value of 10.673%. The extract was spotted on the TLC plate and then eluted with n-hexane : acetone (7:3), then sprayed with citroborate. The ethanol extract was then isolated using KCV method with the eluent ratio nhexane : acetone (10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2: 8, 1:9, 0:10) then tested by thin layer chromatography. The fractionation results were isolated by TLC using n-hexane: acetone (7:3) followed by testing the purity of the isolate using multi-eluent TLC and two-dimensional TLC to see the purity of the compound/isolate. Isolates were identified by interpretation of UV-Vis spectrophotometer data obtained maximum wavelengths of 223 nm and 286 nm and by interpretation of FTIR data it was found that there was an absorption band at wave number 3456.44 indicating O-H groups, at absorption of 1653.00 indicating C=O (ketones), at absorption 1093.64 showed a C-O group, and at absorption 802.39 showed a C-H group and obtained color screening data, TLC screening, and UV-Vis and FTIR spectrophotometric identification as a feature of the presence of flavonoid compounds.